The Antibacterial Activity of Angelica glauca in form of Silver Nanoparticles - Zahraa Sedeeq Qasim; Khadeeja Younis Abid2 (College of Pharmacy University of Baghdad, 2023)
Angelica glauca have been used traditionally as an over the counter herbal preparation, nowadays nanotechnology formulate metal  nanoparticles from  Angelica glauca in green synthesis method which increase Angelica glauca pharmacology and pharmaceutical application. The aims of present work  were to synthesis Angelica glauca silver nanoparticles from its methanolic extract,  phytochemicals detection,  investigation the morphology  and chemical  compound characteristic present in Angelica glauca  AgNPs by spectroscopic method of FT-IR, and scan electron microscope, and   finally in vitro  evaluation the antibacterial activity of Angelica glauca  in forms of  methanolic  extract and  silver nanoparticles. Extraction by soxhlet was the method used in preparation  Angelica glauca methanolic extract, to be use in preparation Angelica glauca silver nanoparticles, 5 phytochemicals  were detected,  in addition to detection Angelica glauca AgNPs characteristic  of active chemical compound and nanoparticles morphology by FT-IR and SEM, in vitro assessment antibacterial activity against Four types of control bacteria. Methanolic extract weight yielded from 250 g of Angelica glauca was 13.3g, in addition to phytochemical detection test was positive for alkaloids, flavonoids, tannins, steroids and coumarins. However, detection of terpenoids, carbohydrate, saponine, quinine, and proteins showed negative result, FT-IR spectroscopy, which  showed a sharp band  with different wave length, indicating the presence of multi- functional group as aliphatic -CH3,  olefinic -C=C-, and  carbonyl C=O, particle size detected by SEM )mean ±SD) was 70.9nm±13.60. The antibacterial  activity of  Angelica glauca AgNPs was higher than methanolic extract. The two formula of Angelica glauca  exhibit a varying degree of antibacterial activity, Angelica glauca contain many bioactive phytochemical compounds when reduced to nanoparticles which can be used in curing health related problems and in many pharmaceutical application across the globe.